CIRCLE: A digital platform for circular food waste management in achieving sustainable food security - Karina Auralia; Ni Luh Ayu Nariswari Dewi; Steffany Marcellia Witanto; Trimono (Journal of Sustainability, Society, and Eco-Welfare, 2026)
Background: Food loss and waste (FLW) pose a major global challenge, threatening food security, economic stability, and environmental sustainability. In Indonesia, despite abundant resources, inefficiencies in production and distribution still lead to significant waste and nutritional inequality. Overcoming this issue requires an integrated and sustainable system that improves redistribution efficiency. Supported by digital innovations such as Artificial Intelligence (AI), the Internet of Things (IoT), and data analytics, the circular economy approach offers a strategic solution. In response, the CIRCLE platform was developed as a smart and sustainable digital system for food redistribution. Methods: This study uses a descriptive method through a literature review to identify theories, concepts, and best practices on circular economy, based digital platforms for reducing FLW. Secondary data from scientific publications and institutional reports were analyzed to form the conceptual basis for designing the CIRCLE (Circular Utilization of Food Resources) platform. Findings: The literature emphasizes the importance of multi-stakeholder collaboration and the application of AI, IoT, and data analytics to develop efficient and sustainable food distribution systems. The implementation of user-centered design and gamification is also recommended to enhance user engagement and awareness. Conclusion: The CIRCLE platform represents an innovative and sustainable digital solution to reduce food waste, strengthen food security, and foster collaboration toward achieving SDG 2 and SDG 12 in Indonesia. Novelty/Originality of this article: This study introduces the CIRCLE platform as a distinctive integration of circular economy principles and digital technologies, including AI, IoT, and gamification, within a unified system for reducing food loss and waste in Indonesia.